RESPON GURU SMA NEGERI PAREPARE TERHADAP PRODUK BANK SYARIAH INDONESIA CABANG PAREPARE - Bunga, Purnamasari; Darmawati, Darmawati; Semaun, Syahriyah; Muliati, Muliati; bahri S, andi; Musmulyadi, Musmulyadi (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2024)
This thesis discusses the response of high school teachers in Parepare to the products offered by the Indonesian Sharia Bank (BSI) Parepare branch. The purpose of this study is to identify the types of BSI products used by high school teachers in Parepare, to analyze their responses to these products, and to examine the factors influencing their responses. The research method employed is qualitative, with a phenomenological approach used to describe the phenomena observed in the field. The study involved 15 informants, and data were collected through observations, interviews, and documentation. The data were then analyzed to present findings and draw conclusions. The results of this study indicate that 1) The types of BSI products used by high school teachers in Parepare include Wadi’ah financing principles, credit products, as well as other Islamic banking services such as savings, financing, and investments, all of which are in accordance with Sharia financial principles. 2) The response of high school teachers in Parepare to the products offered by the BSI Parepare branch varies, but generally shows a positive acceptance. Teachers tend to use BSI products, indicating trust and alignment with the Sharia values they seek. 3) The factors influencing the response of high school teachers in Parepare to BSI products include individual understanding and awareness of Sharia financial principles, personal knowledge, and value considerations. Teachers tend to choose BSI products based on internal deliberations and personal choices, rather than external factors such as recommendations from others.